Religious Coping for Covid-19 Patients: Islamic Approaches - Murtadho, Ali; Hidayanti, Ema; Fakhri, Mohammad; Masri, Subekti; Purwanti, Kristi Liani; Algifahmy, Ayu Faiza; Hakim, Lukmanul (Journal of Al-Tamaddun, 2022)
This qualitative study aims to explore the religious coping of Covid-19 patients during the home care and self-isolation process. A correlative narrative strategy with a sample of 7 Covid-19 patients are used to determining the religious coping of Muslims during the pandemic in the form of praying, reading the Qur’an, dhikr, charity, and having thoughts of Allah. The the result showed that patients need the help of close relatives to develop religious coping and it is essential to provide spiritual healing services in addition to pharmaceutical therapy to Covid-19 patients. Furthermore, Islamic counseling can be used as an alternative to spiritual therapy, while religious coping creates positive psychological conditions, supporting healing and increasing immunity. Further study needs to be carried out to determine the importance of implementing a holistic care model in health services Covid-19.